Tren Temporal dan Visualisasi Spasial Prevalensi Double Burden Malnutrition Anak Indonesia Tahun 2013 dan 2023 - sofi oktaviani; Irda Novrida Ashar (Jurnal Kesehatan Bhakti Husada, 2026)
Introduction: Double Burden of Malnutrition (DBM) refers to the coexistence of undernutrition and overnutrition within the same population. This phenomenon has become a significant public health challenge globally, particularly in developing countries including Indonesia. Objective: This study aimed to examine the temporal trends and spatial distribution of the prevalence of stunting, severe stunting, overweight, and obesity among children in Indonesia between 2013 and 2023.Methods: This study used secondary data from Riset Kesehatan Dasar (Riskesdas) 2013, Riskesdas 2018 and Survei Kesehatan Indonesia (SKI) 2023. Spatial distribution analysis was conducted by combining provincial prevalence data of stunting, severe stunting, overweight, and obesity with geographic polygon data obtained from the Humanitarian Data Exchange (HDX). Data visualization was performed using R version 4.4.1. Results: During the period from 2013 to 2023, the prevalence of stunting among children under five declined from 19.2% to 15.8%, while severe stunting decreased from 18.0% to 5.7%. In contrast, the prevalence of overweight among children aged 5–12 years increased from 10.8% to 11.9%, whereas obesity remained relatively stable (8.0%, 9.2%, and 7.8% in 2013, 2018, and 2023, respectively). Spatially, higher stunting prevalence is still concentrated in eastern Indonesia, whereas overweight prevalence is more prominent in western regions, which tend to have higher levels of urbanization.Conclusion: Indonesia has made progress in reducing stunting prevalence among children; however, the increasing prevalence of overweight has not been overcome properly. Suggestion: More comprehensive and integrated nutrition policies are needed to simultaneously address both undernutrition and overnutrition among children. Keywords: double burden of malnutrition, stunting, overweight, obesity, children.